Efficient Generation of CRISPR/Cas9-Mediated Homozygous/Biallelic Medicago truncatula Mutants Using a Hairy Root System - Zhang, Hailing; Cao, Yingping; Zhang, Huan; Xu, Yue; Zhou, Chuanen; Liu, Wenwen; Zhu, Ruifen; Shang, Chen; Li, Jikai; Shen, Zhongbao; Guo, Siyi; Hu, Zhubing; et al. (Frontiers in Plant Science, 2020)
In the process of acquiring mutants mediated by CRISPR/Cas9,. plantlets are often regenerated from both mutated and non-mutated cells in a random manner, which increase the odds of chimeric mutated plant. In general, it’s necessary to infect more explants or grow to next generation for the need of generating more biallelic or homozygous mutants. In present study, an efficient way of obtaining biallelic or homozygous mutated lines via fast-growing hairy root system without increasing numbers of infected explants or prolonging sexual propagation generation is reported. The fast growing lateral branches of hair roots are originated deep within the parental root from a small number of founder cells at the periphery, and therefore were employed as a library that classify different editing types in different lateral branches in which the homozygous or biallelic lines were screened. Here, MtPDS was employed in a proof-of-concept experiment to evaluate the efficiency of genome editing with our hairy root system. Homozygous/biallelic mutations were found only 1 of the 20 lines in the 1st generation hairy roots, and 8 lines randomly selected were cultured to obtain their branch roots, homozygous/biallelic mutations were found in 6 of the 8 lines in their branch roots. We also tested the method with MtCOMT gene and got the same result. All of the seedlings regenerated from the homozygous/bilallelic hairy root mutation lines of MtPDS displayed albino phenotypes. The entire process from vector design to the recovery of plantlets with homozygous/bilallelic mutations took approximately 4.5-6.5 months. The whole process could bring inspiration for efficiently generating homozygous/biallelic mutants through CRISPR/Cas9 system from the hairy root or root system of a chimeric mutated transformants, especially for the rare and endangered plants whose explants sources are very limited or the plants that lack of tissue culture and rapid propagation system.